Excitation and Propagation of a Fast Pulse Guided Wave in a Circular Dielectric Waveguide - Legenkiy, M.N.; Butrym, A.Yu. (Радиофизика и радиоастрономия, 2013)
It is shown that a pulse signal in a circular dielectric waveguide is partitioned into slow and fast waves. The fast wave propagates along the dielectric surface with the speed of light in free space and creates a precursor field in the dielectric waveguide in the form of cones similar to Cherenkov radiation. These cones are re-reflected at the critical angle between the dielectric interfaces creating a rhombus-shaped wave structure. Long time modeling of this fast wave has been conducted using the Moving Frame Body of Revolution FDTD technique (BOR-FDTD). The revealed peculiarities of the considered wave structure are discussed. Продемонстрировано разделение импульсного сигнала в диэлектрическом волноводе на медленную и быструю волны. Быстрая волна распространяется вдоль поверхности диэлектрика со скоростью света в свободном пространстве и создает предвестник в волноводе в виде конусов, похожих на излучение Черенкова. Эти конусы переотражаются между границами диэлектрика под углом полного внутреннего отражения, создавая ромбическую волновую структуру. Проведено долговременное моделирование этой быстрой волны с использованием метода конечных разностей во временной области для тел вращения в сопровождающем окне. Обсуждаются выявленные особенности поведения рассмотренной волновой структуры. Продемонстровано розділення імпульсного сигналу в діелектричному хвилеводі на повільну та швидку хвилі. Швидка хвиля поширюється вздовж поверхні діелектрика зі швидкістю світла у вільному просторі та створює передвісник у хвилеводі у вигляді конусів, схожих на випромінювання Черенкова. Ці конуси перевідбиваються між границями діелектрика під кутом повного внутрішнього відбиття, утворюючи ромбічну хвилеву структуру. Виконано довгочасове моделювання цієї швидкої хвилі методом скінченних різниць у часовій області для тіл обертання у супроводжуючому вікні. Дискутуються виявлені особливості поведінки розглянутої хвилевої структури.